Primer tRNA3Lys on the viral genome exists in unextended and two-base extended forms within mature human immunodeficiency virus type 1. - Huang, Y (1997)
In human immunodeficiency virus type 1, tRNALys3 is placed upon the primer binding site, where it serves as the primer for reverse transcription. We show herein that genomic placement occurs independently of precursor protein processing and that the placed tRNALys3 exists in two major forms: unextended or in a form extended by the first two DNA bases incorporated, C and T. The two-base extended form of the tRNALys3 is absent in a protease-negative mutant, indicating a requirement for mature viral proteins to initiate reverse transcription within the virus.